The Development of Taxation of Small Business in Russia in the Conditions of the Digital Economy - Zhuravleva, I.A. (Journal of Reviews on Global Economics, 2018)
The subject of the study of the proposed topic of the article is the tax relations arising in the process of tax regulation by states of taxation of small business in the digital economy. The relevance of small business development as one of the important categories of taxpayers plays an essential role in the formation of the revenue side of the budget, as well as in the solution of social issues in society. The novelty of scientific research lies in the fact that the problems of investing and taxing small business are based on the prospects of digitalization of the economy. The purpose of writing this research is to address the identified problems of small business taxation in the rapidly changing information and communication technologies, Internet sites, the emergence of new paradigms and business models. The problems of taxation of self-employed population in the country are touched, anddirections for their solution are determined. When writing the article, general scientific methods of financial, economic, comparative analysis, analytical and systematic approach to the object of research and methodological approaches in a number of proposals were used. Problems are identified and investigated in the scientific context, and an in-depth analysis is conducted to ensure the development of small enterprises in Russia in the digital economy.